PENGARUH TINGKAT PENDIDIKAN PEMILIK, PRAKTIK AKUNTANSI DAN PERSEPSI ATAS INSENTIF PAJAK PPH FINAL DITANGGUNG PEMERINTAH (DTP) TERHADAP KEPATUHAN WPOP UMKM - I Gede Citta Baswara; I Putu Fery Karyada; Anak Agung Ketut Agus Suardika (UNHI Press, 2022)
Abstract The Corona Virus or Covid-19 pandemic has had a major impact on the decline in the global economy in several countries, including Indonesia, including the tax sector. The Covid-19 pandemic has impacted Micro, Small and Medium Enterprises. For example, MSMEs in Denpasar City are the most dominantly affected by Covid-19 with a total of 4,445. The purpose of this study was to determine how the influence of the owner's level of education, accounting practices and perceptions of the government-borne final income tax incentives (DTP) on MSME WPOP compliance. This research is a type of quantitative research. The population in this study is individual taxpayers as MSMEs in Denpasar City. The sample used in this study were 100 respondents. Data processing using multiple linear regression analysis techniques. The results of data analysis are that the owner's education level has no significant effect on MSME WPOP Compliance, while Accounting Practices and Perceptions of the Final DTP PPh Tax Incentives have a significant effect on MSME WPOP Compliance. Keyword : Owner's Education Level, Accounting Practices, and Perception of Government-borne Final Income Tax Incentives (DTP)